Burkholderia genome mining for nonribosomal peptide synthetases reveals a great potential for novel siderophores and lipopeptides synthesis. Issue 3 (5th April 2016) - Esmaeel, Qassim; Pupin, Maude; Kieu, Nam Phuong; Chataigné, Gabrielle; Béchet, Max; Deravel, Jovana; Krier, François; Höfte, Monica; Jacques, Philippe; Leclère, Valérie
Abstract: Burkholderia is an important genus encompassing a variety of species, including pathogenic strains as well as strains that promote plant growth. We have carried out a global strategy, which combined two complementary approaches. The first one is genome guided with deep analysis of genome sequences and the second one is assay guided with experiments to support the predictions obtained in silico. This efficient screening for new secondary metabolites, performed on 48 gapless genomes of Burkholderia species, revealed a total of 161 clusters containing nonribosomal peptide synthetases (NRPSs), with the potential to synthesize at least 11 novel products. Most of them are siderophores or lipopeptides, two classes of products with potential application in biocontrol. The strategy led to the identification, for the first time, of the cluster for cepaciachelin biosynthesis in the genome of Burkholderia ambifaria AMMD and a cluster corresponding to a new malleobactin‐like siderophore, called phymabactin, was identified in Burkholderia phymatum STM815 genome. In both cases, the siderophore was produced when the strain was grown in iron‐limited conditions. Elsewhere, the cluster for the antifungal burkholdin was detected in the genome of B. ambifaria AMMD and also Burkholderia sp. KJ006. Burkholderia pseudomallei strains harbor the genetic potential to produce a novel lipopeptide called burkhomycin, containing a peptidyl moiety of 12 monomers. A mixture of lipopeptides produced by Burkholderia rhizoxinica lowered the surface tension of the supernatant from 70 to 27 mN·m −1 . The production of nonribosomal secondary metabolites seems related to the three phylogenetic groups obtained from 16S rRNA sequences. Moreover, the genome‐mining approach gave new insights into the nonribosomal synthesis exemplified by the identification of dual C/E domains in lipopeptide NRPSs, up to now essentially found in Pseudomonas strains. Abstract : A genome mining was carried out on 48 Burkholderia strains. A bioinformatics screening for nonribosomal peptide synthetases (NRPSs) led to the identification of new secondary metabolites, especially siderophores and lipopeptides.